Spillover and crossover effects of exposure to work‐related aggression and adversities: A dyadic diary study. Issue 1 (25th October 2022) - Herrmann, Alexander; Glaser, Jürgen; Greitemeyer, Tobias
Abstract: The past two decades have produced extensive evidence on the manifold and severe outcomes for victims of aggression exposure in the workplace. However, due to the dominating individual‐centered approach, most findings miss a social network perspective. Consequently, knowledge of negative spillover to different life‐domains or crossover to uninvolved individuals alongside a detailed understanding of the involved transmission processes remains scarce. By integrating social aggression theorizing, the present study investigated transmission routes (emphatic, behavioral) of experienced adversities and aggression at work toward perpetration of aggressive behavior and potential spillover and crossover effects into the private life domain in a diary study of 72 mixed dyads. Analyses of mediation based upon the Actor‐Partner Interdependence Model revealed an association between the frequency of perpetrating aggressive behavior in the work context and a spillover into the private life domain via aggression‐promoting internal states (emotions, cognitions, arousal). Based on the different patterns of mediation, it appears that adversities follow a mental transmission process, whereby experienced aggression displayed behavioral assimilation. In contrast, no crossover effects of exposure to adversities or aggression at work to a study partner at home could be detected. Practical and theoretical implications as well as limitations and ideas for future work are discussed.